PENGARUH MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN (Studi Kasus Di Citra Land Manado) - KUMOWAL, BEUTY FALLON (Sam Ratulangi University, 2014)
Housing is the one of basic needs that people want. As the raising amount of population, thedemand of this product also tent to increase. Results of the F test in this study showed sig F isequal to 0.000 < 0.05, which means the marketing mix consists of product, price, location,and joint promotion has a significant influence on purchasing decisions. Based on the resultsof t-test can be seen that the variable product, price, location, and promotion significantlyinfluence purchasing decisions. T-test results also showed that the location of the variable thas a value and greatest beta coefficient. So the location variables most strongly influencecompared to other variables the variable location has a dominant influence on the purchasedecision structure. Adjusted R Square value in this study was 0.560. This indicates thatapproximately 56% of purchase decisions can be explained by the jour independentvariables, namely Product, Price, Location, Promotion. When the remaining 44% isinfluenced by other variables not examined in this study.